PENGARUH KONSENTRASI EKSTRAK KASAR DAUN PAITAN (Tithonia diversifolia)TERHADAP KEPADATAN POPULASI, INTENSITAS SERANGAN Spodoptera exigua Hubner (LEPIDOPTERA : NOCTUIDAE) DAN PRODUKSI BAWANG MERAH - Megawati, Megawati; Anshary, Alam; Lakani, Irwan (AGROTEKBIS, 2019)
Effective control and friendly to the environment for example the utilization of natural pesticide that is a paitan leaf (Tithonia diversifolia).One of often found pestin red onion plant is Spodoptera exigua Hubner.The aims of this research were to determine the concentration of rough extract of paitan leaves(Tithonia diversifolia) which is best in controlling Spodoptera exigua Hubner pests. This research took place in Oloboju village, Sigi regency, central Sulawesi province and the implementation from May toJuly 2017. Research method using randomized block design (RBD), with 6 treatment that is 0g/1 liter air (without treatment), 2.5 g/1 liter water, 5 g/1 liter water, 7.5 g/1 liter water, 10 g/1 liter water, and 12.5 g/1 liter water and repeated 3 times. The results showed that the amount of population density, intensity of S. exigua attack, and the highest onion production is found in plants without treatmentand the lowest at 12.5 g /1 liter water treatment.T. diversifolia extract was able to control S. exigua larvae which showed a decrease in attack caused by S. exigua larvae with increasing treatment concentration.